METHODS FOR SENTINEL LYMPH NODE DETECTION IN PATIENTS WITH BREAST CANCER - A. D. Zikiryakhodzhaev; T. I. Grushina; M. V. Starkova; L. P. Kazaryan; Yu. I. Volkova; D. V. Bagdasarova; N. V. Ablitsova; N. S. Skreptsova; F. N. Usov (Сибирский онкологический журнал)
Objective: to provide various methods for sentinel lymph node detection considering their advantages and disadvantages.Material and Methods. The search of the relevant articles published in Pubmed, MedLine, RINTs, etc. database was conducted. 49 publications from 1970 to 2018 were analyzed.Results. Currently, sentinel lymph node biopsy (SLN biopsy) has become a worthy alternative to traditional lymphatic surgery for early breast cancer. SLN biopsy significantly decreases the number of postoperative complications caused by lymphadenectomy and improves the quality of life of cancer patients. So far, a large number of SLN detection techniques have accumulated. Each of these techniques has its own advantages and disadvantages.Conclusion. Despite a large number of SLN detection methods, the question of the optimal technique is currently debatable.